Let $x_{i}>0(i=1,2,\cdots,n)$,and such $x_{1}+x_{2}+\cdots+x_{n}=1$,show that $$n-1+\sum_{i=1}^{n}\dfrac{x^2_{i}}{x_{i+1}}\ge\sum_{i=1}^{n}\dfrac{1}{x_{i+1}-x_{i}+1}\tag{1}$$ where $x_{n+1}=x_{1}$

I have use Cauchy-schwarz inequality $$LHS\ge n-1+\dfrac{(x_{1}+x_{2}+\cdots+x_{n})^2}{x_{1}+x_{2}+\cdots+x_{n}}=n$$ so I think maybe have $$\sum_{i=1}^{n}\dfrac{1}{x_{i+1}-x_{i}+1}\le n?$$ But it's a pity that I finally found out use C-S $$\sum_{i=1}^{n}\dfrac{1}{x_{i+1}-x_{i}+1}\ge\dfrac{(1+1+\cdots+1)^2}{\sum_{i=1}^{n}(x_{i+1}-x_{i}+1)}=n$$

So far, I still can't solve this problem (1).


First off, subtract $n$ from both sides to get:

$$LHS = \sum_{i=1}^n\dfrac{x_i(x_i-x_{i+1})}{x_{i+1}}\geq\sum_{i=1}^n\dfrac{x_i-x_{i+1}}{x_{i+1}-x_i+1} = RHS.$$ Now subtract RHS from LHS:

$$LHS-RHS = \sum_{i=1}^n(x_i-x_{i+1})\left(\dfrac{x_i}{x_{i+1}} - \dfrac{1}{x_{i+1}-x_i+1}\right) = \sum_{i=1}^n\dfrac{(x_i-x_{i+1})^2(1-x_i)}{x_i(x_{i+1}-x_i+1)}\geq 0.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.